2011
DOI: 10.1287/mnsc.1110.1317
|View full text |Cite
|
Sign up to set email alerts
|

The Stock Market in the Driver's Seat! Implications for R&D and Marketing

Abstract: The budgets for research and development (R&D) and marketing should be determined by managers to attain product market advantages. However, in response to investor expectations for short-term stock returns, managers may modify these budgets myopically to avoid unexpected short-term earnings shortfalls, at the cost of long-term profitability. We propose that the past behavior of firm stock returns and volatility may create investor expectations of short-term financial performance, which drives managers to modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 75 publications
2
92
0
Order By: Relevance
“…Shifts toward exploitation, and its ability to insulate the firm from immediate threats, reduce a firm's susceptibility to financial market changes. Extant research has shown that investors and shareholders care about risk as well as return when they view a firm's financial outlook (e.g., Chakravarty and Grewal 2011), thus demonstrating the practical and theoretical contribution of this research.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Shifts toward exploitation, and its ability to insulate the firm from immediate threats, reduce a firm's susceptibility to financial market changes. Extant research has shown that investors and shareholders care about risk as well as return when they view a firm's financial outlook (e.g., Chakravarty and Grewal 2011), thus demonstrating the practical and theoretical contribution of this research.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, we rely on the theory to inform our expectations of how SMA shifts affect two critical dimensions of financial performance, idiosyncratic risk and financial return. Idiosyncratic risk involves the projected financial stability resulting from the strategic action of the firm (e.g., Chakravarty and Grewal 2011); financial return demonstrates the magnitude of the return generated by those actions (e.g., . Combined, they provide a comprehensive depiction of the financial repercussions of SMA.…”
mentioning
confidence: 99%
“…However, stock market pressures may encourage firms to reduce their marketing investments to improve their short-term performance (Chakravarty and Grewal 2011). This short-term emphasis is highlighted by Firepond, Inc., a provider of integrated e-business sales and marketing solutions that went public in 2000; to attract investor attention to its initial public offering (IPO), Firepond reduced its marketing investment (advertising and research and development (R&D)) to 69% of revenue (thus increasing earnings) in 2000 compared to 97% of revenue it consistently spent in years prior to and after the IPO.…”
Section: Introductionmentioning
confidence: 99%
“… For the recent survey and evidence, see, for example, Osma and Young () and Chakravarty and Grewal (). A willingness to bypass profitable investments for the meeting of earnings targets (earnings smoothing) was also found by Graham et al.…”
mentioning
confidence: 99%